Peran Tingkat Pendidikan Ibu dan Kelengkapan Imunisasi Dasar terhadap Kejadian Stunting pada Anak - Nita Yulianti Hardiantini; Yuyun Solihatin; Hani Handayani; Ade Kurniawati; Asep Setiawan (Literasi Intelektual, 2026)
Background: Stunting is a chronic nutritional problem among children under five that remains a major public health challenge. Disease prevention through basic immunization plays an important role in supporting optimal growth. Methods: This study employed an analytic observational design with a cross-sectional approach to examine the relationship between maternal education level and completeness of basic immunization, as well as its association with stunting among children under five. A total of 83 children were selected using simple random sampling. Data were collected through structured questionnaires and verification of Maternal and Child Health (MCH) books, then analyzed using the chi-square test. Results:The findings showed that there was no significant relationship between maternal education level and completeness of basic immunization (p = 0.573). However, a significant relationship was found between completeness of basic immunization and stunting incidence (p = 0.046), where children with incomplete immunization were more likely to experience stunting. Conclusion: Completeness of basic immunization plays an important role in stunting prevention. Therefore, strengthening immunization programs and providing continuous health education to families and communities are essential to reduce stunting prevalence.